A method for controllable preparation of metal substrate microstructure surface and prediction of wetting properties
Through the response surface method, the electric spark line cutting parameters were optimized, the pit-protruding composite microstructure was prepared, and the wetting performance simulation model of square cylindrical microarray structure was established, which solved the problem of difficult simulation of the wetting performance of metal matrix surfaces, and realized the High-precision wetting performance prediction and superhydrophobic surface preparation.
Patent Information
- Application Number
- CN202410762651.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-13
AI Technical Summary
There is a lack of effective methods in the prior art to simulate and control the wetting properties of metal matrix surfaces.
The electrical processing parameters of EDM were optimized by the response surface method, and the pit-protruding composite microstructure was prepared through a single pulse discharge model, and a wetting performance simulation model of square cylindrical microarray structure was established.
The controllable preparation and wetting performance of the microstructure surface of the metal matrix is realized, and the prediction accuracy of the simulation model is 97.9%, which expands the application field of electric spark wire cutting and provides guidance on the preparation of superhydrophobic surface of the metal matrix.
Smart Images

Figure CN118752017B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microarray structures, and in particular relates to a method for controllable preparation of a metal substrate microstructure surface and prediction of wetting properties. Background Art
[0002] 6061 aluminum alloy is widely used in various fields due to its excellent properties, such as light weight, high strength, corrosion resistance, good thermal conductivity, and easy processing. Influenced by it, the industrial science and technology field began to apply its self-cleaning ability, frost and ice reduction ability, fluid drag reduction ability, oil-water separation ability and other characteristics. Superhydrophobic surfaces are used in aircraft, ships, weapons and other fields, and their preparation technology has developed rapidly. Cai et al. established a simulation model of the wetting state of water droplets on solid surfaces based on the moving grid two-phase flow method, which includes the fixation, movement and re-fixation of the contact line and takes into account two-dimensional and three-dimensional geometric shapes. Huang et al. used the three-dimensional multiphase lattice Boltzmann method to study the condensation and self-propelled jumping process of droplets on superhydrophobic surfaces with micro-pillar structures, and determined the new phenomenon of secondary coalescence jumping. The results show that wettability has a significant effect on droplet jumping. Gong et al. used the phase field lattice Boltzmann method with a large density ratio to simulate and analyze the wetting properties of solid material surfaces, and discussed in detail the effects of energy barriers and gravity effects on wetting properties. However, after reviewing a large amount of relevant literature, it is found that there is still a lack of simulation research on the wettability of the surface of the prepared metal substrate. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that there is no suitable method for simulating the wettability of metal substrate surfaces, and to provide a method for controllable preparation of metal substrate microstructure surfaces and prediction of wettability.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for controllable preparation of a metal substrate microstructure surface and prediction of wettability, the preparation method comprising the following steps:
[0006] S1: Response surface optimization is performed on the peak current and pulse width of wire EDM machining parameters to find the optimal combination of machining process parameters;
[0007] S2: With the optimal discharge parameter combination, the pit-convex composite microstructure is obtained through the single pulse discharge model ( Figure 4 ) contact angle, at the same time, the pit-protrusion composite microstructure was prepared with this discharge parameter and the contact angle was calculated, and the obtained pit-protrusion composite microstructure contact angle simulation model has high accuracy;
[0008] S3: According to the optimal combination of processing parameters, the contact angle of the pit-protrusion composite microstructure obtained from the above experiment is set as the wetting wall of the square column microarray structure, and a simulation model of the surface wetting performance of the square column microarray structure is established;
[0009] S4: Using 6061 aluminum alloy as the substrate, a square columnar microarray structure was prepared on a high-speed wire-cut EDM machine.
[0010] S5: During post-treatment, low surface energy substance stearic acid (C 18 H 36 O 2 ) is placed in an anhydrous ethanol solution and stirred with a magnetic heating stirrer to finally prepare a 2% stearic acid ethanol solution. The square columnar microarray structure sample obtained in S4 is placed in the stearic acid ethanol solution and allowed to soak for 6 hours in a laboratory environment.
[0011] S6: The simulation model of the surface wetting performance of the square pillar microarray structure is highly accurate, and the difference between the surface contact angle of the sample obtained from the S5 experimental results is less than 2.1%. It is concluded that the simulation model of the surface wetting performance of the square pillar microarray structure prepared by wire electric discharge cutting (WEDM) has extremely high accuracy.
[0012] Furthermore, in the step S2, during the preparation of the high-speed wire-cut electric discharge machine, the processing parameters adopted are: processing voltage of 80V, discharge current of 16A, pulse width of 32μs, and pulse interval of 1:7.
[0013] Furthermore, in the step S2, the obtained simulation model of the contact angle of the pit-protrusion composite microstructure has high accuracy and is highly consistent with the contact angle of the pit-protrusion composite microstructure obtained by the mathematical equation and the experimental results.
[0014] Furthermore, in step S3, the contact angle is 126.012°.
[0015] Furthermore, in step S3, the simulation model of the surface wetting performance of the square columnar microarray structure is a fluid-solid coupling model.
[0016] Furthermore, in step S5, the so-called laboratory environment is a temperature controlled at 20±5°C, a humidity controlled at 65±15%RH, and the laboratory is kept ventilated and the air is fresh and clean.
[0017] Furthermore, in step S5, after the immersion is completed, a Theisken scanning electron microscope (SEM) is used to characterize the surface morphology and chemical elements of the sample, and an OCA20 video optical contact angle meter is used to record the contact angle of a 5 μL water droplet on the sample surface for 10 s.
[0018] The beneficial effects of the present invention compared to the prior art are:
[0019] 1. In the present invention, the response surface method and the electric spark wire cutting single pulse discharge heat flow coupling simulation model are used to solve the blank in simulating the surface wetting characteristics of metal substrates. First, by determining the optimal discharge parameters of the contact angle of the material pit-protrusion composite microstructure, a square columnar microarray structure with good surface wetting performance is prepared; secondly, a super hydrophobic surface of the square columnar microarray structure is successfully prepared on a 6061 aluminum alloy substrate, and a numerical calculation model of the surface wetting performance of the pit-protrusion composite microstructure is established. The influence of structural parameters on the apparent contact angle is explored in detail, and the consistency between the experimental results and the simulation model is compared. Finally, the results show that the prediction accuracy of the simulation model reaches 97.9%. This method not only expands the application field of WEDM, but also provides a theoretical reference for the design of metal substrate microstructure surface, realizes the controllable preparation of metal substrate microstructure surface and the accurate prediction of wetting performance, which has important guiding significance for the preparation of super-hydrophobic surface of metal substrate; the contact angle of the pit-protrusion composite microstructure prepared under the conditions of processing voltage of 80V, discharge current of 16A, pulse width of 32μs, and pulse interval of 1:7 reaches a maximum value of 126.012°, and this discharge parameter is the optimal discharge parameter. The reliability of the simulation model and mathematical equation of the contact angle of the pit-protrusion composite microstructure was verified by the central composite experiment, and the optimal discharge parameters were used for the preparation of square columnar microarray structure.
[0020] 2. In the present invention, the water droplets on the square columnar microarray structure conform to the Cassie-Baxter wetting state; under the condition of a column spacing of 400 μm and a column height of 2000 μm, as the column width increases from 300 μm to 500 μm, the simulation and experimental results of the contact angle of the square columnar microarray structure decrease from 156.5° to 140.2° and from 156.7° to 143.2°, respectively; under the condition of a column width of 400 μm and a column height of 2000 μm, as the column spacing increases from 300 μm to 500 μm, the simulation and experimental results of the contact angle of the square columnar microarray structure decrease from 156.5° to 140.2° and from 156.7° to 143.2°, respectively. To 500μm, the simulation and experimental results of the contact angle of the square pillar microarray structure decreased from 151.3° to 142.8° and from 152.3° to 145.8° respectively; the accuracy of the simulation model of the surface wetting performance of the square pillar microarray structure is high, and the difference with the experimental results is less than 2.1%. The simulation model of the surface wetting performance of the square pillar microarray structure prepared by WEDM has extremely high accuracy, thereby improving the accuracy of the product obtained, and providing great convenience for people to prepare super hydrophobic surfaces of metal substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a simulation diagram of the surface morphology of a single discharge micro-pit of the present invention;
[0022] Figure 2A schematic diagram of the single discharge micro-pit size parameters of the present invention;
[0023] Figure 3 It is an equivalent model of the surface morphology of the pit-protrusion composite microstructure in the present invention, and its arrangement position and top view;
[0024] Figure 4 The contact angle characterization diagram of the pit-protrusion composite microstructure prepared by the optimal discharge parameter combination in the present invention;
[0025] Figure 5 A schematic diagram of the micro-pit contact angle obtained by the simulation model, mathematical equations, and experimental results in the present invention;
[0026] Figure 6 A simulation model diagram of a water droplet falling on a square columnar microarray structure in the present invention;
[0027] Figure 7 A diagram showing the boundary condition settings of a water droplet falling on a simulation model of a square columnar microarray structure in the present invention;
[0028] Figure 8 A diagram showing the grid division of a simulation model of a water droplet falling on a square columnar microarray structure in the present invention;
[0029] Fig. 9 Schematic diagram of simulation results of the effect of the width of the square pillars on the surface wetting properties of the square pillar microarray structure of the present invention;
[0030] Fig.10 Schematic diagram of simulation results of the effect of the distance between square pillars on the surface wetting properties of the square pillar microarray structure in the present invention;
[0031] Fig.11 Schematic diagram of 6061 aluminum alloy wire cutting processing in the present invention;
[0032] Fig.12 A two-dimensional microscopic morphology characterization diagram of the overall situation of the square columnar microarray structure of the present invention;
[0033] Fig.13 A two-dimensional microscopic morphology characterization diagram of nine square pillars in the square pillar microarray structure of the present invention;
[0034] Fig.14 A two-dimensional microscopic morphology characterization diagram of a single square pillar in the square pillar microarray structure of the present invention;
[0035] Fig.15 This is a two-dimensional microscopic morphology characterization diagram of a part of the square columnar microarray structure of the present invention magnified 2000 times;
[0036] Fig.16 This is a contact angle characterization diagram of the square columnar microarray structure sample 1 of the present invention;
[0037] Fig.17 This is a contact angle characterization diagram of the square columnar microarray structure sample 2 of the present invention;
[0038] Fig.18 This is a contact angle characterization diagram of the square columnar microarray structure sample 3 of the present invention;
[0039] Fig.19 This is a contact angle characterization diagram of the square columnar microarray structure sample 4 of the present invention;
[0040] Fig. 20 This is a contact angle characterization diagram of the square columnar microarray structure sample 5 of the present invention;
[0041] Fig.21 This is a contact angle characterization diagram of the square columnar microarray structure sample 6 of the present invention;
[0042] Fig. 22 It is a contact angle characterization diagram of the square columnar microarray structure sample 7 of the present invention;
[0043] Fig.23 This is a contact angle characterization diagram of the square columnar microarray structure sample 8 of the present invention;
[0044] Fig.24 It is a contact angle characterization diagram of the square columnar microarray structure sample 9 of the present invention;
[0045] Fig.25 This is a characterization diagram of the rolling angle of the square columnar microarray structure sample 1 with a contact angle greater than 150° in the present invention;
[0046] Fig.26 This is a characterization diagram of the rolling angle of the square columnar microarray structure sample 2 with a contact angle greater than 150° in the present invention;
[0047] Fig. 27 This is a characterization diagram of the rolling angle of the square columnar microarray structure sample 3 with a contact angle greater than 150° in the present invention;
[0048] Fig.28 This is a characterization diagram of the rolling angle of the square columnar microarray structure sample 6 with a contact angle greater than 150° in the present invention;
[0049] Fig.29 This is a characterization diagram of the rolling angle of the square columnar microarray structure sample 7 with a contact angle greater than 150° in the present invention;
[0050] Fig.30 Schematic diagram of the effect of column width on the contact angle of the square columnar microarray structure in the present invention;
[0051] Fig.31 Schematic diagram of the effect of the column spacing on the contact angle of the square columnar microarray structure in the present invention. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0053] In the present invention, the response surface method and the electric spark wire cutting single pulse discharge heat flow coupling simulation model are used to solve the blank in simulating the wetting characteristics of the metal substrate surface. By determining the optimal discharge parameters of the contact angle of the composite material pit-protrusion composite microstructure, a square columnar microarray structure with good surface wetting performance is prepared, and a super hydrophobic surface of the square columnar microarray structure is successfully prepared on a 6061 aluminum alloy substrate, and a numerical calculation model of the wetting performance of the pit-protrusion composite microstructure surface is established. This method not only expands the application field of WEDM, but also provides a theoretical reference for the design of the metal matrix microstructure surface, realizes the controllable preparation of the metal matrix microstructure surface and the accurate prediction of the wetting performance, which has important guiding significance for the preparation of the metal matrix super hydrophobic surface.
[0054] Embodiment 1:
[0055] Combination Figure 1-31 , a method for controllable preparation of metal substrate microstructured surfaces and prediction of wetting properties.
[0056] In WEDM processing, the peak current I p With pulse width T on It is an important parameter that affects the processing effect and the surface performance of the workpiece. By studying their influence on the contact angle of the pit-protrusion composite microstructure through the response surface method, the optimal discharge parameter combination can be found, the processing process can be optimized, and the processing accuracy and wetting performance of the workpiece surface can be improved, thereby improving the processing quality and performance. The response surface method can clarify the optimization direction and range of parameters, avoid blindly adjusting parameters, improve processing efficiency and workpiece quality, and reduce processing costs and resource waste.
[0057] The present invention uses Design-Expert 12.0 software to perform a two-factor three-level response surface experiment, and selects the peak current I p With pulse width T on As a factor, the experimentally measured value θ 1 is the response value. -1, 0, and 1 are used to represent the different levels of each factor for coding. The diameter a of a single discharge micro-pit-protrusion structure and the distance b between the two protrusion structures are obtained through response surface design, and then the contact angle θ of the pit-protrusion composite microstructure of the corresponding experiment is calculated by formula (1): 1Table 1 shows the correspondence between the coding values and the experimental values of each factor, and the response surface design and results are shown in Table 2.
[0058]
[0059] Where: θ 1 is the contact angle of the pit-protrusion composite microstructure under the Cassie-Baxter wetting state, °; θ 0 is the intrinsic contact angle, °.
[0060] Table 1 Specific parameters of response surface design
[0061]
[0062] Table 2 Response surface design and simulation results
[0063]
[0064]
[0065] The regression model of contact angle was established, and its variance and significance analysis were obtained, as shown in Table 3. The F value of the model was 45.46, the P value was <0.0001, and the F value and P value of lack of fit were 2.85 and 0.1686, respectively, indicating that the model has extremely high significance. At the same time, the model determination coefficient R 2 , Adjusted determination coefficient R 2 The prediction coefficient R 2 They are 0.9701, 0.9488 and 0.8375 respectively, the three values are close and have little difference from 1, and the signal-to-noise ratio is 24.0867, which is much greater than 4, indicating that the model is real, reliable and has good response. Therefore, the regression equation of the contact angle of the pit-protrusion composite microstructure is basically accurate.
[0066] Table 3 Variance and significance of contact angle
[0067]
[0068] Among them: when P<0.001, it means that the factor is highly significant; when P<0.05, it means that the factor is significant; when P≥0.05, it means that the factor is not significant.
[0069] According to the variance and significance analysis of the contact angle of the pit-protrusion composite microstructure, the coefficients of the mathematical equation were calculated and the regression equation was obtained as follows:
[0070] θ 1 =+32.93092+6.82052I p +2.01998T on -0.053794×I p ×Ton
[0071] -0.128647×(I p ) 2 -0.017584×(T on ) 2 (2)
[0072] Discharge parameters when the contact angle of the pit-protrusion composite microstructure is optimal: peak current I p is 16A, pulse width T on The contact angle of the concave-convex composite microstructure can reach a maximum value of 128.216°.
[0073] In order to verify the accuracy of the contact angle prediction model of the continuous discharge surface of wire EDM and the contact angle regression equation of the pit-protrusion composite microstructure surface based on the response surface method, 7 groups of different discharge parameters were selected for experimental processing, and the contact angle of the pit-protrusion composite microstructure surface was measured. The DK7632 high-speed wire EDM machine was used to prepare the samples. The discharge parameters were: processing voltage 80V, discharge current 16A, pulse width 32μs, and pulse interval 1:7. The electrical parameters of the microstructure samples used in the experiment are shown in Table 5. It is found that the maximum contact angle of the pit-protrusion composite microstructure can reach 126.012°, as shown in Table 5. Figure 4 shown.
[0074] Depend on Figure 5 It can be seen that the contact angles of the pit-protrusion composite microstructure obtained by the simulation model, mathematical equation, and experimental results have a high degree of consistency. The relative error rate between the simulation model of the single-pulse discharge heat-flow coupling simulation model of the electrical discharge wire cutting and the contact angle of the pit-protrusion composite microstructure obtained by the experiment ranges from 1.28% to 4.82%, and the average relative error rate is 3.05%. The relative error rate between the mathematical equation formula (2) and the heat source temperature obtained by the experiment ranges from 1.75% to 3.24%, and the average relative error rate is 2.50%. In general, the simulation model of the contact angle of the pit-protrusion composite microstructure has a high accuracy, and the mathematical equation of the contact angle of the pit-protrusion composite microstructure and the electrical parameters obtained based on the response surface method also has a high accuracy.
[0075] Table 5 Electrical parameters of the microstructure samples used in the experimental verification
[0076]
[0077] Through simulation and experiment, the discharge parameter when the contact angle of the pit-protrusion composite microstructure is the largest, that is, the peak current I p is 16A, pulse width T onThe discharge time is 32 μs, which is the optimal discharge parameter and will be used in the simulation and experiment of the surface wetting performance of the square columnar microarray structure.
[0078] Construct a simulation model of the surface wetting performance of a square columnar microarray structure:
[0079] Under the conditions of a peak current of 16A and a pulse width of 32μs, the contact angle of the pit-protrusion composite microstructure reaches a maximum value of 126.012°. Since the pit-protrusion composite microstructures prepared above have not reached the superhydrophobic state, and lack submillimeter microstructures. The square columnar microarray structure consists of a submillimeter array column structure and a micron-scale pit-protrusion composite microstructure. Through simulation, the influence of different microarray structure parameters on the wetting performance is evaluated before actual preparation. Therefore, the COMSOL5.6 software was used to construct a simulation model for simulation. Taking the microarray structure with a column width, column spacing, and column height of 300μm, 400μm, and 2000μm, respectively, as an example, a water droplet with a volume of 5μL is released near the surface of the square columnar microarray structure. There are three different material forms in the water droplet falling model: solid, liquid, and gas. The simulation geometry model selects the part within the red dotted box for multi-physics field coupling simulation. Figure 6 This is a water droplet falling model. The simulation model area is set to laminar flow and gravity, the blue boundary is set to an open boundary, the green boundary is set to a wetted wall, the contact angle of the wetted wall is set to 126.012°, and the boundary conditions are set as follows Figure 7 The mesh is refined for the water droplet and substrate surface, and the mesh is sparse for the air phase, with the maximum and minimum unit sizes being 2.55×10 -2 mm and 7.6×10 -5 mm, the maximum element growth rate is 1.05, the curvature factor is 0.2, the narrow area resolution is 1, and the mesh division is as follows Figure 8 The simulation model environment temperature is set to 293.15K, and the pressure is set to 1 standard atmosphere, that is, 1.013×10 5 Pa, air is defined as fluid 1, and water droplets are defined as fluid 2.
[0080] The control equation of the fluid satisfies the Navier-Stokes equation as shown in Formula 3. Considering the influence of the microstructure size effect, the surface tension of the gas-liquid interface needs to be added to the Navier-Stokes equation as a volume force source term.
[0081]
[0082] Where: I is the unit matrix; μ is the dynamic viscosity of the fluid material, Pa·s; P is the pressure of the fluid material, Pa; F is the body force source term, N; g is the gravitational acceleration, m / s 2 ; ρ is the fluid density; u is the fluid velocity; t is the time; is the gradient operator;
[0083] The surface tension of the gas-liquid interface is the product of the chemical potential and the gradient of the phase field parameter:
[0084]
[0085] Where: F s is the surface tension of the gas-liquid interface, N; G is the chemical potential, J / m 3 ; φ is the phase field parameter.
[0086] The expressions of the remaining control equations can be expressed as:
[0087] The Cahn-Hilliard equation is used to track the diffusion interface between two immiscible fluids:
[0088]
[0089] Where: γ is the mobility, (m 3 ·s) / kg; λ is the mixing energy density, N; ψ is the phase field auxiliary variable; ε is the interface thickness control parameter, m; φ is a function;
[0090] The relationship between surface tension coefficient, mixing energy density and interface thickness control parameters:
[0091]
[0092]
[0093] Where: σ is the surface tension coefficient, N / m; h c is the characteristic mesh size passing through the interface area.
[0094] Volume fraction of air and water:
[0095]
[0096] Where: V 1 is the volume fraction of air; V 2 is the volume fraction of water.
[0097] Density and dynamic viscosity of gas-liquid two-phase interface fluid:
[0098] ρ=ρ 1 V 1 +ρ 2 V 2 (11)
[0099] μ=μ 1 V 1 +μ 2 V 2(12)
[0100] Where: 1 is the density of air, kg / m 3 ρ 2 is the density of water, kg / m 3 ;μ 1 is the dynamic viscosity of air, N·s / m 2 ;μ 2 is the dynamic viscosity of water, N·s / m 2 .
[0101] Wetted Wall:
[0102]
[0103] Where: θ a is the contact angle of the wetted wall, °; n is the normal vector.
[0104] Simulation Results Analysis
[0105] (1) The influence of the width of the square column on the surface wetting properties of the square column microarray structure
[0106] The column widths of the square columns are 300μm, 350μm, 400μm, 450μm and 500μm respectively. The column spacing and column height of the square columns are controlled to be 400μm and 2000μm respectively. The peak current is 16A and the pulse width is 32μs. The simulation results are as follows: Fig. 9 As the column width increases from 300 μm to 500 μm, the simulation results of the contact angle of the square column microarray structure show a gradually decreasing trend, and the simulation results of the contact angle decrease from 156.5° to 140.2°, and the water droplets on the square column microarray structure conform to the Cassie-Baxter wetting state.
[0107] (2) The influence of the square column spacing on the surface wetting properties of the square column microarray structure
[0108] The column spacing of the square column is 300μm, 350μm, 400μm, 450μm and 500μm respectively, and the column width and column height of the square column are controlled to be 400μm and 2000μm respectively. The same electrical parameters as above are used, and the simulation results are as follows Fig.10 As the column spacing increases from 300μm to 500μm, the simulation results of the contact angle of the square column microarray structure show a gradually decreasing trend, and the simulation results of the contact angle decrease from 151.3° to 142.8°, and the water droplets on the square column microarray structure also conform to the Cassie-Baxter wetting state.
[0109] The method for preparing a super-hydrophobic microstructure material with good wetting performance according to the above experimental parameters comprises the following steps:
[0110] 6061 aluminum alloy was used as the substrate to prepare the square column microarray structure on a high-speed wire-cut electric discharge machine. The sample size parameters are shown in Table 6. The optimal discharge parameters were used during the preparation process: the processing voltage was 80V, the discharge current was 16A, the pulse width was 32μs, and the pulse interval was 1:7. The post-treatment method was a combination of low surface energy modification and heat treatment. The low surface energy substance stearic acid (C 18 H 36 O 2 ) is placed in an anhydrous ethanol solution, and then stirred with a magnetic heating stirrer to prepare a 2% stearic acid ethanol solution. The cut samples are placed in a stearic acid ethanol solution and soaked for 6 hours in a laboratory environment, wherein the temperature of the laboratory environment is controlled at 20±5°C, the humidity is controlled at 65±15%RH, and the laboratory is ventilated and the air is fresh and clean. A Theisken scanning electron microscope (SEM) is used to characterize the surface morphology and chemical elements of the samples. The contact angle of a 5μL water droplet on the sample surface is recorded with an OCA20 video optical contact angle meter for 10s.
[0111] Table 6 Dimensional parameters of square column microarray structure samples
[0112]
[0113] The prepared super-hydrophobic microstructure material was characterized and analyzed for its microarray structure, and the two-dimensional microscopic morphology of the square columnar microarray structure was characterized by a Theisken scanning electron microscope. Figure 12-15 As shown. Its structure shows a relatively uniform column width and column spacing size and distribution, and the microstructure is rich. It was observed that the actual column width is smaller than the design value, the actual column spacing is larger than the design value, and the processing error range is between 10μm and 20μm. The pit-convex composite microstructure prepared by wire EDM is mainly composed of irregular pits, ellipsoidal convexities, wrinkles and tiny pores. The irregular pits are produced by high-frequency continuous pulse discharge during the wire EDM process. The ellipsoidal convexities are formed when the molten material splashes out during the processing and then adheres to the surface of the workpiece and cools down. The wrinkles are formed by the cooling of the molten material during the processing. The tiny pores are formed by the presence of a small amount of air in the molten material as the molten material cools.
[0114] (1) Experimental results of contact angle of square column microarray structure
[0115] The contact angle of each sample of the square column microarray structure was characterized by using an OCA20 video optical contact angle measuring instrument. Figure 16-24As shown. The experimental results of the contact angles of samples 1 to 5 show a gradually decreasing trend, and the experimental results of the contact angles decrease from 156.7° to 143.2°. The experimental results of the contact angles of samples 6 to 9 also show a gradually decreasing trend, and the experimental results of the contact angles decrease from 152.3° to 145.8°, and the water droplets on the square columnar microarray structure also conform to the Cassie-Baxter wetting state. When a water droplet is placed on the surface of the square columnar microarray structure, there is a large amount of air between the two square columnar microstructures to form an air cushion, which has a certain supporting effect on the water droplet, so that the solid-liquid contact area between the water droplet and the square columnar microarray structure is smaller than the solid-liquid contact area between the water droplet and the pit-protrusion composite microstructure. According to the Cassie-Baxter model, the contact angle of the square columnar microarray structure is greater than the contact angle of the pit-protrusion composite microstructure.
[0116] (2) Experimental results of the rolling angle of the square column microarray structure
[0117] The rolling angle of the square columnar microarray structure sample with a contact angle greater than 150° was characterized by an OCA20 video optical contact angle meter. Figure 25-29 shown.
[0118] As can be seen from the figure, the rolling angle of the square columnar microarray structure shows a trend of gradually decreasing with the increase of the contact angle. The rolling angles of samples 1, 2, 3, 6 and 7 are all less than 10°, and all have reached a superhydrophobic state.
[0119] Comparison of experimental and simulation results:
[0120] (1) Effect of column width on contact angle of square column microarray structure
[0121] The size parameters of the square column microarray structure during the simulation and experimental research are: column widths are 300μm, 350μm, 400μm, 450μm, and 500μm, column spacing is 400μm, and column height is 2000μm. Fig.30 It can be seen that as the column width increases from 300 μm to 500 μm, both the simulation results and the experimental results of the contact angle of the square columnar microarray structure show a gradually decreasing trend. The simulation result of the contact angle decreases from 156.5° to 140.2°, and the experimental result of the contact angle decreases from 156.7° to 143.2°.
[0122] (2) Effect of column spacing on contact angle of square column microarray structure
[0123] The size parameters of the square column microarray structure during the simulation and experimental research are: the column width is 400μm, the column spacing is 300μm, 350μm, 400μm, 450μm, 50μm, and the column height is 2000μm. Fig.31It can be seen that as the column spacing increases from 300μm to 500μm, both the simulation results and the experimental results of the contact angle of the square columnar microarray structure show a gradually decreasing trend. The simulation result of the contact angle decreases from 151.3° to 142.8°, and the experimental result of the contact angle decreases from 152.3° to 145.8°.
[0124] (3) Error analysis between simulation and experimental results
[0125] The simulation model of the surface wetting performance of the square columnar microarray structure has a high accuracy and the difference with the experimental results is less than 2.1%, which shows that the simulation model of the surface wetting performance of the square columnar microarray structure is accurate. The simulation results of the contact angle of the square columnar microarray structure are smaller than the experimental results. The main reasons for the inconsistency between the two are as follows:
[0126] a) Simplification of microstructure model: In the numerical simulation process, in order to simplify the calculation or reduce the calculation cost, the microstructure is simplified. The complex three-dimensional morphology of the microarray structure is simplified into a two-dimensional model, while the complexity of the actual microstructure is ignored.
[0127] b) Uncertainty of geometric parameters of microstructures: The geometric parameters of the microarray structure, such as the height and spacing of the square columnar microarray structure, directly affect the wetting properties of its surface. However, in the actual preparation process, the wire EDM technology may be affected by factors such as processing accuracy and equipment performance when preparing microstructures, resulting in deviations between the geometric parameters of the actual microstructure and the designed values, resulting in the solid-liquid contact area between the water droplets and the total contact area being smaller than that of the designed square columnar microarray structure.
[0128] c) Experimental error and measurement uncertainty: Due to the existence of certain random errors and systematic errors in the experiment, the measurement results often have certain uncertainties. This uncertainty may lead to deviations in the experimental results, thus affecting the evaluation of the wetting properties of the microarray structure surface.
[0129] According to the above experimental results, it can be known that: In the present invention, the response surface method and the electric spark wire cutting single pulse discharge heat flow coupling simulation model are used to solve the gap in simulating the surface wetting characteristics of metal substrates. By determining the optimal discharge parameters of the contact angle of the material pit-protrusion composite microstructure, a square columnar microarray structure with good surface wetting performance is prepared. The super-hydrophobic surface of the square columnar microarray structure was successfully prepared on the 6061 aluminum alloy substrate, and a numerical calculation model of the surface wetting performance of the pit-protrusion composite microstructure was established. The influence of structural parameters on the apparent contact angle was explored in detail, and the consistency of the experimental results and the simulation model was compared. The results show that the prediction accuracy of the simulation model is 97.9%. This method not only expands the application field of WEDM, but also provides a theoretical reference for the design of metal matrix microstructure surface, realizes the controllable preparation of metal matrix microstructure surface and the accurate prediction of wetting performance, which has important guiding significance for the preparation of metal matrix superhydrophobic surface; the contact angle of the pit-protrusion composite microstructure prepared under the conditions of processing voltage of 80V, discharge current of 16A, pulse width of 32μs, and pulse interval of 1:7 reaches a maximum value of 126.012°, and this discharge parameter is the optimal discharge parameter. The reliability of the simulation model and mathematical equation of the composite microstructure is verified by the central composite experiment, and the optimal discharge parameters are used for the preparation of square columnar microarray structure.
[0130] In the present invention, water droplets on the square columnar microarray structure conform to the Cassie-Baxter wetting state; under the condition that the column spacing is 400 μm and the column height is 2000 μm, as the column width increases from 300 μm to 500 μm, the simulation and experimental results of the contact angle of the square columnar microarray structure decrease from 156.5° to 140.2° and from 156.7° to 143.2°, respectively; under the condition that the column width is 400 μm and the column height is 2000 μm, as the column spacing increases from 300 μm to 500 μm, the simulation and experimental results of the contact angle of the square columnar microarray structure decrease from 151.3° to 142.8° and from 152.3° to 145.8°, respectively; the simulation model of the surface wetting performance of the square columnar microarray structure has high accuracy and the difference with the experimental results is less than 2.1%.
[0131] In the present invention, a simulation model of the surface wetting performance of a square columnar microarray structure prepared by WEDM is established with extremely high accuracy.
[0132] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0133] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for controllable preparation of metal substrate microstructure surface combined with wettability prediction, characterized in that: The preparation method comprises the following steps: S1: Response surface optimization is performed on the peak current and pulse width of wire EDM machining parameters to find the optimal combination of machining process parameters; S2: The contact angle simulation model of the pit-protrusion composite microstructure is obtained by using the optimal combination of processing parameters through the single pulse discharge model. At the same time, the pit-protrusion composite microstructure is prepared with this optimal combination of processing parameters and the contact angle is calculated. The obtained contact angle simulation model of the pit-protrusion composite microstructure has high accuracy. In the preparation process of the high-speed wire-cut electric discharge machine, the processing parameters used are: processing voltage of 80V, discharge current of 16A, pulse width of 32μs, and pulse interval of 1:
7. S3: The contact angle of the pit-protrusion composite microstructure prepared by the optimal processing parameter combination in S2 is set as the wetting wall of the square column microarray structure, and a simulation model of the surface wetting performance of the square column microarray structure is established; S4: Using 6061 aluminum alloy as the substrate, a square columnar microarray structure was prepared on a high-speed wire-cut EDM machine. S5: During post-treatment, the low surface energy material stearic acid is placed in an anhydrous ethanol solution, and stirred with a magnetic heating stirrer to finally prepare a 2% mass fraction stearic acid ethanol solution. The square columnar microarray structure sample obtained in S4 is placed in the stearic acid ethanol solution and allowed to soak for 6 hours in a laboratory environment.
2. The method for controllable preparation of metal matrix microstructure surface combined with wettability prediction according to claim 1, characterized in that: In the step S2, the obtained contact angle simulation model of the pit-protrusion composite microstructure has high accuracy and is highly consistent with the contact angle of the pit-protrusion composite microstructure obtained from the mathematical equation and the experimental results.
3. The method for controllable preparation of metal matrix microstructure surface combined with wettability prediction according to claim 1, characterized in that: In the step S3, the contact angle is 126.012°.
4. The method for controllable preparation of metal matrix microstructure surface combined with wettability prediction according to claim 1, characterized in that: In the step S3, the simulation model of the surface wetting performance of the square columnar microarray structure is a fluid-solid coupling model.
5. The method for controllable preparation of metal substrate microstructure surface combined with wettability prediction according to claim 1, characterized in that: In step S5, the so-called laboratory environment is a temperature controlled at 20±5°C, a humidity controlled at 65±15%RH, and the laboratory is kept ventilated and the air is fresh and clean.
6. The method for controllable preparation of metal substrate microstructure surface combined with wettability prediction according to claim 1, characterized in that: In the step S5, after the immersion is completed, the surface morphology and chemical elements of the sample are characterized using a Theisken scanning electron microscope, and the contact angle of a 5 μL water droplet on the sample surface is recorded using an OCA20 video optical contact angle meter for 10 seconds.